Karakterisasi Mutu Es Krim Ubi Jalar Ungu Dengan Penstabil Tepung Porang - Zainuri Zainuri; Yeni Sulastri; I K Yudha Gautama (Indonesian, 2020)
This study aims to determine the effect of porang flour concentration on the quality characteristics of purple sweet potato ice cream. This research was used an experimental method and was design as a Completely Randomized Design (CRD) with 6 (six) treatments of porang flour concentrations (0; 0.1; 0.2; 0.3; 0.4; 0.5 %) and each treatment was repeated 3 (three) times. The parameters observed included the overrun, resistance, protein content, fat content, total solids, color, flavor, texture, and the taste of ice cream. The data were analised using Analysis of variance (ANOVA) at the 5% level using the Co-stat software. When significantly different, the data were further analised using the Honest Significant Difference (HSD) at the level of 5%. The results revealed that the use of porang flour had a significantly different effect on the protein content, total solids, resistance, and texture, but did not give a significant effect on the fat content, overrun, color, odor and the taste of purple sweet potato ice cream. The treatment of 0.2% porang flour was the best treatment that produced ice cream with the protein content 5.25%, fat content 16.53% and total solids 52.30%, overrun 2.95%, resistance 39.98 minutes and organoleptic characteristics (color, odor, texture and taste) were preferred by the panelists.